Immunomodulatory Drugs (IMiDs) in Multiple Myeloma - Raza, Shahzad; A. Safyan, Rachael; Lentzsch, Suzanne (Current Cancer Drug Targets, 2017)
Background: Multiple myeloma (MM) is a hematological cancer caused by a proliferation of clonal plasma cells, leading to anemia, renal failure, hypercalcemia and destructive bone lesions resulting in significant morbidity. The overall survival has significantly improved with the incorporation of immunomodulatory drugs (IMiDs) and proteasome inhibitors (PI). Objective: Here we provide a comprehensive review on IMiDs including molecular mechanisms, recent advances in therapeutic applications and management of toxicities in the treatment of MM. Methods: Relevant publications in peer reviewed journals were retrieved by a selective search of PubMed. Systemic reviews, meta-analyses, randomized controlled trials, and treatment recommendations were reviewed and are summarized here. Results: Thalidomide, a first generation IMiD, is associated with significant toxicity in older patients. Lenalidomide, a more potent second generation IMiD with fewer side effects than thalidomide, is commonly used in newly-diagnosed multiple myeloma, relapsed refractory myeloma and as maintenance therapy after autologous stem cell transplantation (ASCT). Pomalidomide, a third generation IMiD, is 10 times more potent than lenalidomide and has shown impressive results in relapsed MM patients and in those refractory to both lenalidomide and bortezomib. Conclusion: The clinical use of IMiDs in MM has significantly improved long-term survival and quality of life. Future studies are looking into novel biomarkers predictive of outcome in MM and new combinations of lenalidomide and pomalidomde with PI, monoclonal antibodies, immune checkpoint blockers and several other chemotherapies.
Keywords: Immunomodulatory drugs